Usability in the admission monitoring system of an emergency room - Rocha, Hertaline Menezes do Nascimento; Nascimento, Ester Batista do; Santos, Laryssa Carvalho dos; Alves, Guilherme Viturino; Farre, Anny Giselly Milhome da Costa; Santana-Filho, Valter Joviniano de (Revista de Saúde Pública, 2021)
OBJECTIVE To develop and evaluate the usability of the admission monitoring system in an emergency room. METHODS This applied research intends to develop a software product and evaluate its usability. The development followed four stages: systematic review, structuring of the system framework, construction of system forms, and evaluation of the information generated. In the evaluation, the experts simulated the use of the system by inserting data from a fictitious medical record. We measured usability using the System Usability Scale (SUS). Scores and scores were calculated individually and globally. We propose these evaluation standards: worst case scenario, poor, average, good, excellent, and best-case scenario. RESULTS The Sistema de Informação e Monitoramento das Internações em Pronto-Socorro (SIMIPS - Information and Monitoring System for Emergency Room Admissions) monitors the epidemiological profile of admissions to the emergency room, time management, clinical deterioration, incidence of adverse events, and human resource management. The usability of SIMIPS, evaluated by 17 experts, reached the SUS Score 86.5 (best case scenario), and some suggestions for modifications were accepted. CONCLUSIONS We consider SIMIPS an easy-to-use tool, with real importance in the management of emergencies in view of overcrowding and congestion problems faced in Brazil.